The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1123/jsep.32.5.694
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Doping Intentions in Elite-Level Athletes: A Social Cognition Approach

Abstract: Doping use is an ongoing problem in contemporary sports. Despite efforts to detect and control doping, research on its etiology is limited, especially among elite-level athletes. The present study used an integrated social cognition model to examine the predictors of doping intentions. Structured anonymous questionnaires were completed by 1075 Greek adult elite-level athletes (M age = 25 years, SD = 5.89, 36.1% females) from both team and individual sports. Multiple regression and mediation analyses showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 35 publications
13
136
2
7
Order By: Relevance
“…We used self-efficacy to refrain from doping instead of perceived behavioral control as they both reflect efficacy beliefs. Further, past evidence has shown that self-efficacy to refrain from doping is a stronger predictor of doping intentions [16] and, in contrast to perceived behavioral control, a significant predictor of doping intentions in both users and non-users [94]. This model did not fit well [95]:  2 (3) = 288.98, p < 0.001, comparative fit index (CFI) = 0.92, root mean square error of estimation (RMSEA) = 0.14, standardized root mean square residual (SRMR) = 0.04.…”
Section: Path Analyses Of a Theory Of Planned Behavior Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…We used self-efficacy to refrain from doping instead of perceived behavioral control as they both reflect efficacy beliefs. Further, past evidence has shown that self-efficacy to refrain from doping is a stronger predictor of doping intentions [16] and, in contrast to perceived behavioral control, a significant predictor of doping intentions in both users and non-users [94]. This model did not fit well [95]:  2 (3) = 288.98, p < 0.001, comparative fit index (CFI) = 0.92, root mean square error of estimation (RMSEA) = 0.14, standardized root mean square residual (SRMR) = 0.04.…”
Section: Path Analyses Of a Theory Of Planned Behavior Modelmentioning
confidence: 98%
“…Researchers utilizing TPB have documented the ability of doping attitudes, perceived behavioral control and subjective norms to predict doping intention and self-reported doping behavior [e.g., [15][16][17]. These studies have involved a variety of populations including elite athletes [16], gym users [18], and adolescents [17,19]; suggesting generalizability of findings across different samples and settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affective self-regulatory efficacy: Affective self-regulatory efficacy was evaluated using the items from the French version of the Social Skills Rating System (SSRS) [35][36][37][38], which was adapted to the sports context while preserving the highest semantic similarity to the original version. Sixteen items measured self-efficacy to regulate positive affect (5 items; e.g., "I feel capable of expressing my joy when positive things happen to me") and negative affect (12 items; e.g., "I feel capable of controlling myself when I am angry") on a Likert scale from "Not at all capable" (1) to "Completely capable" (6).…”
Section: Motivation In Sportmentioning
confidence: 99%
“…Scenarios have been used in previous doping research [13,35] because they do not require athletes to reveal their true behavior and can refer to various doping situations [16]. We based our approach on both the series of scenarios developed by Zelli et al [15] and the items used to measure doping intentions in past research [3,36]. The participating adolescents and young adults read five hypothetical scenarios concerning doping intentions.…”
Section: Doping Intentionsmentioning
confidence: 99%